PET/CT Imaging as a Diagnostic Tool in Distinguishing Well-Differentiated versus Dedifferentiated Liposarcoma. (1st June 2020) - Parkes, Amanda; Urquiola, Elizabeth; Bhosale, Priya; Lin, Heather; Watson, Kelsey; Wang, Wei-Lien; Feig, Barry; Torres, Keila; Roland, Christina L.; Conley, Anthony P.; Zarzour, Maria; Livingston, J. Andrew; et al.
Abstract : Distinguishing well-differentiated liposarcoma (WDLPS) from dedifferentiated liposarcoma (DDLPS) is essential given distinct treatment paradigms and chemosensitivity. Percutaneous biopsy has a low sensitivity for detecting DDLPS. We sought to identify the diagnostic utility of positron emission tomography/computed tomography (PET/CT) in identifying WDLPS versus DDLPS. An independent radiologist reviewed PET/CT images to identify target lesions and determine the maximum standardized uptake value (SUVmax). An independent pathologist review confirmed WDLPS or DDLPS histology. A binary cutoff point of SUVmax was identified using a classification and regression trees (CART) algorithm. We identified 20 patients with WDLPS or DDLPS with 26 PET/CTs performed for separate recurrences that were followed by surgical sampling. Of the 26 records, 12 were DDLPS (46%) and 14 were WDLPS (54%). Patients with DDLPS had significantly higher SUVmax than those with WDLPS (p value = 0.0035). A SUVmax of 4 was identified as the cutoff point. Using this cutoff, the sensitivity of SUVmax identifying a case as DDLPS was 83.3% (95% CI: 51.6%, 97.9%) and the specificity was 85.7% (95% CI: 57.2%, 98.2%). PET/CT is a sensitive and specific diagnostic tool to identify the presence of dedifferentiation within the tumor.